REORIENTASI MAKNA MADRASAH DALAM PENDIDIKAN ISLAM - Tharaba, M. Fahim (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Madrasah is the part of islamic education institution needs to up date myself for excise and isn’t part of history only. Madrasah needs to reorientation myself, it is role myself to agent of change and agent of concervation, it bisics for (1) values orientation, (2) social demand orientation, (3) work orientation, (4) child oreintation, dan (5) future and science and technology.